Limited participation and consumption-saving puzzles: A simple explanation and the role of insurance☆ - Gormley, Todd; Liu, Hong; Zhou, Guofu (Journal of Financial Economics, 2010)
In this paper, we show that the existence of a large, negative wealth shock and insufficient insurance against such a shock could explain both the limited stock market participation puzzle and the low-consumption–high-savings puzzle. We then conduct an empirical analysis on the relation between household portfolio choices and access to private insurance and various types of government safety nets. The empirical results demonstrate that a lack of insurance against large, negative wealth shocks is positively correlated with lower participation rates and higher saving rates. Overall, the evidence suggests an important role of insurance in household investment and savings decisions.